EFEKTIVITAS JAHE MERAH UNTUK MENGURANGI NYERI DISMENOREA - Rila Rindi Antina; Dian Eka Januriwasti; Siti Rochimatul Lailiyah (STIKES NGUDIA HUSADA MADURA, 2020)
Dysmenorrhea is a symptomatic phenomenon including abdominal pain, cramps, and back pain. Gastrointestinal symptoms such as nausea and diarrhea can occur as menstrual symptoms (Kusmiran, 2012). The incidence of menstrual pain in the world is very large. On average, more than 50% of women in every country experience menstrual pain. The method used to carry out community service is by collecting data on the number of young women who experience menstruation at Bangkalan High School, then conducting school visits equipped with a pain scale score examination. Mentoring for adolescents is carried out every day during the menstrual period until the symptoms of dysmenorrhoea are reduced and subsided. The assistance was continued with the provision of red ginger drink, knowledge about menstruation and reproductive health, treatment of menstrual periods, sharing with family, moderate exercise and others. The mentoring participants were 20 young women with dismenorhoeing at SMA Bangkalan. After several days of mentoring, some teenagers showed improvement in their dysmenorrhea condition until recovery. Teenagers are able to carry out activities and some treatments around menstruation.